Seroprevalence and assessment of public awareness of Brucella spp., Toxoplasma gondii and Chlamydia abortus in small ruminants from selected smallholder commercial farms of Zimbabwe - Tarusikirwa, Dey F.; Blacklaws, Barbara; Trotter, Caroline L. (PloS one, 2023)
Brucella spp., Toxoplasma gondii , and Chlamydia abortus have long been recognized as zoonoses and significant causes of reproductive failure in small ruminants globally. A cross-sectional study was conducted in August 2020 to determine the seroprevalences of Brucella spp., Toxoplasma gondii and Chlamydia abortus in 398 small ruminants from four districts of Zimbabwe (Chivi, Makoni, Zvimba, and Goromonzi) using Indirect-ELISAs. A structured questionnaire was used to assess the knowledge, attitudes, and practices of 103 smallholder farmers towards small ruminant abortions, Brucella spp., T . gondii and C . abortus , and to obtain a general overview of the significance of small ruminant reproductive failure(s) on their livelihoods. The overall seroprevalences were: 9.1% (95% CI: 6.4–12.3) for Brucella spp., 6.8% (95% CI: 4.5–9.7) for T . gondii and 2.0% (95% CI: 0.9–3.9) for C . abortus . Location, age, parity, and abortion history were associated with Brucella spp. seropositivity. Location was also associated with both T . gondii and C . abortus seropositivity. The questionnaire survey established that 44% of respondents had recently faced reproductive disease challenges within their flocks, with 34% correctly identifying abortion causes and only 10%, 6% and 4% having specific knowledge of Brucella spp., C . abortus and T . gondii , respectively. This study provides the first serological evidence of Brucella spp. in small ruminants since 1996 and builds the evidence on small ruminant toxoplasmosis and chlamydiosis in Zimbabwe. Evidence of these zoonoses in small ruminants and the paucity of knowledge shows the need for a coordinated One Health approach to increase public awareness of these diseases, and to establish effective surveillance and control measures. Further studies are required to establish the role these diseases play in small ruminant reproductive failure(s), to identify the Brucella spp. detected here to species/subspecies level, and to assess the socio-economic impact of reproductive failure in livestock among marginalised rural communities.